2019
DOI: 10.1108/mrr-04-2018-0183
|View full text |Cite
|
Sign up to set email alerts
|

Empowering leadership and job performance: mediating role of psychological empowerment

Abstract: Purpose The purpose of this paper is to check the effects of empowering leadership on job performance of employees through the mediation of psychological empowerment. Design/methodology/approach Primary data were gathered from 418 Indian banking employees. Statistical techniques like factor analysis, multiple regressions and bootstrapping via PROCESS were used to analyze the data. Findings Initially, the results of multiple regression analysis revealed that empowering leadership behaviors have positive inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
123
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(171 citation statements)
references
References 52 publications
12
123
1
9
Order By: Relevance
“…Several studies have examined the impact of psychological empowerment (i.e., intrinsic motivation) on work satisfaction [23,24], organizational commitment [25,26] and performance [27,28]. Moreover, recent studies have confirmed that the higher the level of employees' psychological empowerment, the more motivated employees are to perform well and demonstrate more at work [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the impact of psychological empowerment (i.e., intrinsic motivation) on work satisfaction [23,24], organizational commitment [25,26] and performance [27,28]. Moreover, recent studies have confirmed that the higher the level of employees' psychological empowerment, the more motivated employees are to perform well and demonstrate more at work [29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…As a mediating variable, Employee Empowerment was also used in a study that affected the job satisfaction of employees. Similarly, empowerment has also been used as a mediating variable in several other studies (Carless, 2004;Kundu et al, 2019;Qing et al, 2019). For example, in a study conducted previously, psychological empowerment was found as a mediating variable in the relationship between leadership and employee's attitude towards the job , and it has also been taken as a mediating variable in the relationship between the independent variable i.e.…”
Section: Mediating Effect Of Employee Empowermentmentioning
confidence: 98%
“…If one observes keenly, the employees of a bank are mostly engaged in public dealing and relationship management. If these employees are happy and satisfied with their job, they will keep the customers satisfied otherwise, their attitudes will reflect in their demeanor towards the customers (Kundu, Kumar & Gahlawat, 2019). Traditionally, banks tend to invest in training their employees because well-trained and skilled employees are one of the main priorities of the banking system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have supported the argument that psychological empowerment is related to performance and job satisfaction [23][24] [25] The effects of perceived authentic leadership and core self-evaluations on organizational citizenship behavior: The role of psychological empowerment as a partial mediator. The research conducted by research [26] [27][28] [29] in particular reported that empowerment has a positive and significant influence on employee performance through employee job satisfaction so that it can be stated that empowerment encourages employees to be more active and triggers their creativity. Employees who feel empowered then will have satisfaction in their job.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%